Analisis Coping Stres pada Generasi Y Sandwich Generation di Desa Jatimulya Kecamatan Suradadi Kabupaten Tegal - Astuti, Eva Windi; Sucipto, M. Arif Budiman; Mulyani, Mulyani Mulyani (Universitas PGRI Semarang, 2025)
The sandwich generation are individuals who simultaneously care for their elderly parents and children, often resulting in physical and emotional stress. The research aims to analyze the types, influencing factors, impact of stress, and coping strategies used by generation Y sandwich generation. This research uses a qualitative phenomenological research method by collecting data from three individuals who are part of the sandwich generation in Jatimulya Village and three supporting informants. The results of the research show that the types of stress experienced by generation Y sandwich generation have all been experienced, namely eustress, distress, hyperstress and hypostress, but generally the type of stress experienced tends to be positive stress (eustress). The influencing factors are the environment, individuals and organizations. The impact of stress in its implementation has an impact on the physical, emotional or mental, and work. The coping strategies used are good in implementing problem focused coping and emotion focused coping. However, generally they do not show awareness of unhealthy habits or behavior patterns that are applied with maladaptive coping.Keywords: coping stres, generation Y, sandwich